Hardnekkig hetero: ‘Seksuele diversiteit’ in de praktijk van het middelbaar schoolonderwijs - Meerhoff, Sam (Religie & Samenleving, 2016)
Since 2012, Dutch schools have been legally obliged to teach about sexual diversity. Yet, little is known about how this is implemented. Based on classroom observations, semi-structured interviews with teachers and content analysis of teaching materials, this article analyzes secondary-school teachers’ discourse and practices. It was found that sexual diversity remains a marginalized subject, which is usually discussed in merely one of a series of lessons on sexuality that makes part of the biology curriculum. Both in faith-based and in non-religious schools, teachers primarily aim at showing students how LGBT-people are discriminated against, and at making them reflect on how to respond if someone close to them were to come out as being gay. An unintended consequence of this approach is that it reconfirms heterosexuality as a norm, and fails to empower LGBT-students.